Participant profiles and symptom responses in the initial stages of a South African Mental health managed care programme - Hattingh, Leandri (Department of Psychiatry and Mental Health, 2020)
Introduction Continuously rising health care and workplace costs associated with mental illness is demanding attention from health care funders in South Africa’s private health care sector. The majority of mental health care costs are generated by in-hospital care, whilst funded access to ambulatory care is limited in this sector. The Medscheme Mental Health Programme (MMHP) is a collaborative care project which aims to promote the integration of good quality mental health care into the primary care setting. In a “treatment-to-target” approach, symptom score trackers are used to systematically monitor response to treatment in order to help identify and modify suboptimal treatment plans timeously (Hattingh 2017b). Aims This study describes the MMHP participants and pathways into and through the MMHP, and its initial clinical outcomes. Methods Principal members and dependant beneficiaries of two participating medical schemes screened for enrolment on the MMHP between 1 August 2016 and 28 February 2018 were included in the study. Persons younger than 18 years were excluded. Symptoms of major depressive disorder (MDD), generalised anxiety disorder (GAD), posttraumatic stress disorder (PTSD) and alcohol abuse were screened for by using the Patient Health Questionnaire-9 (PHQ-9) (Spitzer, Williams, and Kroenke 2002-2015; Kroenke and Spitzer 2002), the Generalised Anxiety Disorder Questionnaire-7 (GAD-7) (Spitzer, Williams, and Kroenke 2002-2015; Spitzer and Kroenke 2006), the Primary Care Post-Traumatic Stress Disorder Screen (PC-PTSD) US Department of Veteran Affairs (2015); (Prins, Ouimette, and Kimerling 2003) and the Alcohol Use Disorders Identification Test (AUDIT) (Babor et al. 2001). The Medscheme Care Manager administered these questionnaires telephonically to screen candidates for enrolment on the Programme and communicated regularly with the associated clinical practitioner regarding treatment response. A specialist psychiatrist reviewed and provided recommendations on problematic cases at set intervals. Using logistic regression, the association between demographic characteristics and scheme type and the presence of moderate or severe symptoms of 1) depression, 2) generalised anxiety disorder, and 3) post-traumatic stress disorder, was assessed. Percentages of the sample with a single condition, one, two and three comorbidities were also analysed, as well as the proportions of co-occurrence per various combinations of conditions. Wilcoxon signed rank tests were used to determine the change in symptom severity between baseline and 10 weeks in those receiving intervention through the MMHP. Linear regression models were created to analyse the predictors of change in clinical scores. Results In the screened group, 48.6% were found to have moderate to severe symptoms of anxiety on the GAD-7, 53.2% of depression on the PHQ-9, and 33.2% of PTSD on the PC-PTSD. Relatively high rates of possible comorbidity were found in this study, especially between depression and anxiety: of those screening positive for any one condition, 73.8% screened positive on the combination of PHQ-9 and GAD-7. Screening positive on the PHQ-9 was found to be a very strong predictor of concomitant positive screening on the GAD-7 (OR = 36.4, CI = 25.3 - 52.2), and vice versa - screening positively on the GAD-7 strongly predicted positive screening on the PHQ-9 (OR = 36.6, CI = 25.4 - 52.6). Strong associations were demonstrated with females and potential depression (OR = 1.51, CI = 1.03 - 2.21) and/or PTSD (OR = 1.65, CI = 1.18 - 2.31), while younger age was significantly associated with higher likelihood of screening positive for potential depression (OR: 0.99, CI= 0.98 - 1.00), PTSD (OR = 0.97, CI 0.96 - 0.98) and/or generalised anxiety disorder (OR = 0.97, CI = 0.96 - 0.98). There were statistically and clinically significant improvements in clinical scores for all four conditions at Week 10 after enrolment on the MMHP, compared to baseline: 21% reduction in mean scores in the AUDIT, 43% in the GAD-7, 45% in the PHQ-9, and 36% in the PC-PTSD. Conclusion In its current form, the MMHP appears to be successful in reaching significantly symptomatic medical scheme beneficiaries, with possible scope to expand its reach. Certain key design elements such as using clinical data to determine risk and need for intervention, treatment target calculation adjusted for baseline, screening for comorbidity, and current referral sources, appear to be appropriate. Given the absence of a control group, however, further research is required to confirm the outcomes of the intervention.